Using of Social Media as An Account to The Information Needs - Solihat, Manap; Agustina, Lena (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The mobility of modern society is fast and massive, mass transportation is considered as solution in resolving mobility. One of the mass transportation commonly used in Jabodetabek is KRL. KRL Commuter Line is a commuter Electric Train service operated by PT Kereta Commuter Indonesia (PT KCI). By implementing the digital platform, seeks to develop and improve services to the community with the popularity of social media. This research uses a quantitative method with a survey. The population was taken from the followers of the @commuterline Instagram account. The results showed that the relationship between the message content variable (X1) to the information needs fulfillment variable (Y) was moderate, the relationship between the timeliness variable (X2) and the information needs fulfillment variable (Y) was weak, the relationship between the effectiveness variable ( X) on the cognitive needs variable (Y1) was high, the relationship between the effectiveness variable (X) and the affective needs variable (Y2) was moderate, and the relationship between the effectiveness variable (X) and the information needs fulfillment variable (Y) was high The conclusion of this study is that there is a relationship between the use of Instagram @commuterline social media accounts with the fulfillment of information needs for followers, PT KCI’s Instagram account is able to provide answers to information needs for its customers. The suggestion that can be considered is that the management of the Instagram @commuterline PT. KCI account can be faster in updating the information disseminated to customers and could immediately.